2018
DOI: 10.3348/kjr.2018.19.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy and Prognostic Factors of Transarterial Chemoembolization Plus Microwave Ablation versus Transarterial Chemoembolization Alone in Patients with a Large Solitary or Multinodular Hepatocellular Carcinomas

Abstract: ObjectiveTo evaluate the efficacy and prognostic factors associated with transcatheter arterial chemoembolization (TACE) combined with microwave ablation (MWA) versus TACE alone for a large solitary or multinodular hepatocellular carcinomas (HCCs).Materials and MethodsThis retrospective study involved 258 patients with a large solitary or multinodular HCCs (not more than 10 tumors) who underwent TACE + MWA (n = 92) or TACE alone (n = 166) between July 2011 and April 2015. Local tumor control, survival outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 42 publications
8
40
0
Order By: Relevance
“…Consistent with previously studies, our analysis demonstrates that an add‐on resection or ablation after initial TACE significantly extended the survival time and increased the percentage of patients who reached a 3‐year survival time . This suggests that add‐on resection/ablation works synergistically with TACE.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with previously studies, our analysis demonstrates that an add‐on resection or ablation after initial TACE significantly extended the survival time and increased the percentage of patients who reached a 3‐year survival time . This suggests that add‐on resection/ablation works synergistically with TACE.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the add-on resection or ablation removes or necrotizes hypovascular HCC lesions that are refractory to cytotoxicity by TACE delivered chemicals. 57,58 In further analysis, vascular invasion was the only risk factor that compromised the long-term survival in patients who received the add-on resection and/or ablation after TACE. This finding reveals that the efficacy of the add-on resection and/ or ablation is effective in eliminating almost all of the factors that are required to achieve the 3-year survival in the group without resection and/or ablation after TACE.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, a limited number of studies reported the long-term outcomes of TACE-MWA for large HCCs. Zheng et al reported mediumterm outcomes of TACE-MWA in 92 patients with large HCCs, with a 3-year OS rate of 32.6% [35]. In that study, 44 (47.8%) patients exhibited HCC lesions with a maximum diameter >10 cm, and tumor size was confirmed as a significant predictor of OS.…”
Section: Discussionmentioning
confidence: 83%